Spatial Analysis of Pistachio Cultivates (Growth Period) in Iran - mahmood Hosseinzadeh kermani; Bohlul Alijani; Zahra bigom Hejazizadeh; Mohammad Saligheh (تحقیقات کاربردی علوم جغرافیایی)
The main aim of this paper is to determine the capable areas for cultivating pistachio through considering of Geo statistical Analysis the major effective factors. The necessary climatic daily data of weather stations For the 300 synoptic stations, the station was set up by 2016. The topographic data include relief, slope, aspect, and TIN layers extracts from 1:250000 topographic maps of the region. The maps of land use and vegetation land cover were prepared from the 1:250000 maps of national soil and water Research Institute. The spatial analysis facilities of GIS were utilized for numerical calculation and the spatial geodatabase of the region was established. Then spatial and description data was entered into the data bank. Finally by overlaying analysis in ArcGIS, cultivated area was classified according to its capabilities. The results showed that 707273/88 KM2 Of the area (43%), Not suitable for spreading pistachio cultivation (Including altitudes and urban use and steep slopes, seaside and riverside streams, shoals, saline and swampy lands) and 585130/39 KM2 (35/57%) From the country of Iran Area Including plain areas and agricultural use) was recognized as suitable for the expansion of pistachio cultivation. These areas are located in the east and south east, center and northeastern Iran.